Temporal Characteristics of Visual Processing in Amblyopia - Hu, Xia; Qin, Yi; Ying, Xiaoxiao; Yuan, Junli; Cui, Rong; Ruan, Xiaowei; He, Xianghang; Lu, Zhong-Lin; Lu, Fan; Hou, Fang (Frontiers in Neuroscience, 2021)
Purpose: Amblyopia affects not only spatial vision but also temporal vision. In this study, we aim to investigate temporal processing deficits in amblyopia. Methods: Twenty amblyopic patients (age: 27.0 ± 5.53 years, 15 males), and 25 normal observers (age: 25.6 ± 4.03 years, 15 males) were recruited in this study. Contrast thresholds in an orientation discrimination task in five target-mask stimulus onset asynchronies (SOA) conditions (16.7 ms, 33.4 ms, 50.0 ms, 83.4 ms, and ∞/no noise) were measured. An elaborated perceptual template model (ePTM) was fit to the behavioral data to derive the temporal profile of visual processing for each participant. Results: There were significant threshold differences between the amblyopic and normal eyes (F(1, 43) = 10.6, p = 0.002) and a significant group × SOA interaction (F(2.75, 118) = 4.98, p = 0.004), suggesting different temporal processing between the two groups. The ePTM fitted the data well . Compared to the normal eye, the amblyopic eye had a lower template gain (p = 0.046), and a temporal window with lower peak and broader width (all ps < 0.05). No significant correlation was found between the observed temporal deficits and visual acuity in amblyopia (ps > 0.50). Similar results were found in the anisometropic amblyopia subgroup. No significant difference was found between the fellow eyes of the monocular amblyopia and the normal eyes. Conclusion: Amblyopia is less efficient in processing dynamic visual stimuli. The temporal deficits in amblyopia, represented by a flattened temporal window, are likely independent of spatial vision deficits.